External protection for the emerging market economies? The case for financial liberalisation instead of import barriers in Eastern Europe - Holger Schmieding (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
The main points of this paper are that the case for transitional import barriers for the EMEs is very weak; neither a discriminatory regional payments union nor a uniform import tariff nor a differentiated tariff schedule designed in accordance with the presumed adjustment difficulties are warranted. A radical liberalisation of the financial system in the EMEs is much better suited to promote and smooth the adjustment to market conditions than any scheme for transitional protection. The paper is organised as follows: at first, the major arguments for transitional protection are addressed; thereafter, various schemes for the protection of the tradable goods sector are analysed; ultimately, a proposal for radical financial liberalisation as a superior substitute for trade protection is presented.
Keywords: 330; Kapitalmarktliberalisierung; Protektionismus; Systemtransformation; Osteuropa